TI_GERICHTE 12.2008.69 vom 25. Mai 2009 , Appalto - creditoria e ipoteca legale - nessun litisconsorzio necessario - appello - TI Tribunale d'appello (2009)
Appalto - creditoria e ipoteca legale - nessun litisconsorzio necessario - appello